Transition Metal Catalyzed Carbonylative Synthesis of Heterocycles - Wu, Xiao-Feng.; Beller, Matthias; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The series Topics in Heterocyclic Chemistry presents critical reviews on present and future trends in the research of heterocyclic compounds. Overall the scope is to cover topics dealing with all areas within heterocyclic chemistry, both experimental and theoretical, of interest to the general heterocyclic chemistry community. The series consists of topic related volumes edited by renowned editors with contributions of experts in the field. All chapters from Topics in Heterocyclic Chemistry are published Online First with an individual DOI. In references, Topics in Heterocyclic Chemistry is abbreviated as Top Heterocycl Chem and cited as a journal.
Ru-and Rh-catalyzed carbonylative synthesis of heterocycles -- Pd-catalyzed carbonylative synthesis of five-membered heterocycles from aryl halides -- Pd-catalyzed carbonylative synthesis of six-membered heterocycles from aryl halides -- Pd-catalyzed carbonylative synthesis of other-membered heterocycles from aryl halides -- Carbonylative synthesis of heterocycles via radical process -- Synthesis of heterocycles via oxidative carboynlation.
Keywords: Organometallic chemistry .; Chemistry, Organic; Catalysis; Organometallic Chemistry; Organic Chemistry; Catalysis